Polypharmacy in Older Adults: The Hazard of Hospitalization and Mortality is Mediated by Potentially Inappropriate Prescriptions, Findings From the Moli-sani Study - Costanzo, Simona; Di Castelnuovo, Augusto; Panzera, Teresa; De Curtis, Amalia; Falciglia, Stefania; Persichillo, Mariarosaria; Cerletti, Chiara; Donati, Maria Benedetta; de Gaetano, Giovanni; Iacoviello, Licia, the Moli-sani Investigators (International Journal of Public Health, 2024)
We evaluated the impact of polypharmacy on health in community-dwelling older adults.Methods: We prospectively analysed 5,631 individuals from the Moli-sani study (51% men, aged ≥65 years, recruitment 2005-2010, follow-up 2005-2020). Exposure was categorized as chronic polypharmacy therapy (C-PT; ≥5 therapeutic groups and >2 daily defined doses (DDDs)) or nonchronic polypharmacy therapy (NC-PT; polypharmacy but ≤2 DDDs). Hospitalization and mortality were the main outcomes. The mediating role of the potential inappropriate prescriptions (PIPs) was examined.Results: Compared to individuals not in polypharmacy, those in NC-PT and C-PT had higher hazards of mortality [21% (95%CI 7%-37%) and 30% (16%-46%), respectively] and hospitalization [39% (28%-51%) and 61% (49%-75%), respectively]. Similar results were found for cardiovascular outcomes. PIPs mediated the association between polypharmacy and outcomes, with mediation effects ranging from 13.6% for mortality to 6.0% for hospitalization. Older adults without multimorbidity experienced same harm from multiple medications than those with multimorbidity.Polypharmacy is associated with higher hazard of mortality and hospitalization, with PIPs playing an important role. Addressing "medication without harm" requires assessing drug prescription appropriateness and monitoring for adverse effects.